Surface morphology engineering of metal-oxide films by chemical spray pyrolysis - Rodríguez, Juan (2007)
Chemical Spray Pyrolysis Technique and a combination of sol-gel and spray pyrolysis techniques have been used in order to monitor the morphology of metal-oxide-based thin films to be used as functional materials. We can get from specular to rough-porous surfaces according to the physical-chemical conditions of the precursor / spraying solution. We have produced coatings of ZnO-based and NiOx-based coatings from alcoholic and water solution. A single glass, ITO-precoated glass or alumina was used as the substrate. Porous materials of WO3, CuWO4-x and SnO2 have been produced spraying either inorganic or metal alkoxide gels over a hot substrate. Morphology of coatings were evaluated by either SEM or optical measurements.